Eksplorasi Persepsi Pelanggan Terhadap Kualitas Produk, Kualitas Layanan, Dan Customer Experience Pada Umkm Vinchoco Surabaya: Pendekatan Studi Kualitatif - Adyatma Syammakh, Zayyan; Ariyono Putra, M. Rizal; Surya Adriansyach, Wisnuwardhana; Haidan Faza, Chrisna; Ayub Arrafah, Thaariq (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2026)
This study aims to conduct an in-depth exploration of how customers of Vinchoco Surabaya perceive product quality, service quality, and customer experience within the context of a digital-based micro and small enterprise (MSME). The research employs a qualitative descriptive approach utilizing a purposive sampling technique. Data collection was carried out through triangulation methods, including in-depth interviews with loyal customers, participatory observation of digital platform interactions, and document analysis of online reviews and social media content. The gathered data were subsequently analyzed using Interpretative Phenomenological Analysis (IPA) to interpret the profound meanings embedded in the participants' subjective experiences. The findings reveal three key insights. First, product quality is perceived through the consistent delivery of delicious and premium chocolate taste, supported by elegant packaging and innovative, attractive product variations. Second, service quality is rated highly, particularly in terms of responsiveness, friendliness, and effective communication during the digital ordering and delivery processes. Third, the overall customer experience is characterized by enjoyable, professional interactions that successfully build long-term trust and emotional attachment. The synergy among these three dimensions creates a robust ecosystem of value. This synergy not only fosters high customer loyalty but also shapes the perception of Vinchoco's competitive advantage as a premium brand within the growing MSME chocolate market. The findings of this study provide a theoretical contribution to the understanding of experiential value in the context of micro-scale digital economies. Simultaneously, they offer significant practical implications for MSME entrepreneurs.